2019
DOI: 10.9734/ijtdh/2019/v37i430169
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Vector Abundance and the Incidence of Malaria Parasite amongst Students Living in Nnamdi Azikiwe University Hostels

Abstract: Introduction: Malaria remains an important public health disease in both tropical and subtropical countries of Africa where transmission is mainly through the bite of an infected female Anopheles mosquito. Aim: The main aim of this study was to determine the prevalence of malaria parasite and the abundance of malaria vectors in and around the university hostels.  Place and Duration of Study: The study was carried out in some selected hostels of Nnamdi Azikiwe University, Awka, from the month of Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
4
2
0
Order By: Relevance
“…From our findings, the males have a higher prevalence rate (62.2%) than their female counterparts (54.7%), even though the difference is not statistically significant. The high percentage prevalence observed in the male student in the present study agrees with what was reported by Ezihe et al (2019) and Ezugbo-Nwobi et al (2011) among Azikiwe's University students. Similarly, Adepeju (2017) reported a high prevalence among Federal University Of Technology students, Akure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…From our findings, the males have a higher prevalence rate (62.2%) than their female counterparts (54.7%), even though the difference is not statistically significant. The high percentage prevalence observed in the male student in the present study agrees with what was reported by Ezihe et al (2019) and Ezugbo-Nwobi et al (2011) among Azikiwe's University students. Similarly, Adepeju (2017) reported a high prevalence among Federal University Of Technology students, Akure.…”
Section: Discussionsupporting
confidence: 92%
“…GJPAS/Volume 1/Issue 2/Jul -Dec/2022 infects people worldwide in tropical and subtropical areas, mainly in Sub-Saharan Africa (Ezihe et al, 2019). Malaria is a parasitic infection caused by several Plasmodium species.…”
mentioning
confidence: 99%
“…More so, the hyper activities of the females along with exposed body part especially in the night, as a result of wearing skirts, to mosquito bites, may be responsible. This is in tandem to a study done by Ezihe et al (2019) which recorded an alarmingly high (90%) prevalence of malaria among students of Nnamdi Azikiwe University and this was as a result of night activities among the students thereby exposing them to mosquito bites, but this is in contrast to studies carried out in Federal University of Technology, Akure and Nnamdi Azkiwe University (Ezugbo et al 2011; Awosolu et al 2020), where the prevalence of malaria among the male gender was higher than that of females due to the fact that the males expose their bodies more than the females when the weather was hot and thus increased the chances of being bitten by the mosquitoes.…”
Section: Discussionsupporting
confidence: 85%
“…More so, the hyper activities of the females along with exposed body part especially in the night, as a result of wearing skirts, to mosquito bites, may be responsible. This is in tandem to a study done by Ezihe, et al [22] which recorded an alarmingly high (90%) prevalence of malaria among students of Nnamdi Azikiwe University and this was as a result of night activities among the students thereby exposing them to mosquito bites, but this is in contrast to studies carried out in Federal University of Technology, Akure and Nnamdi Azkiwe University [16,23], where the prevalence of malaria among the male gender was higher than that of females due to the fact that the males expose their bodies more than the females when the weather was hot and thus increased the chances of being bitten by the mosquitoes.…”
Section: Sources Of Information On Sexually Transmittedsupporting
confidence: 91%